Removal of chromium (III) metal ions from fertilizer wastewater using kaolin clay (Journal of Pure and Applied Sciences (Science Forum), 2026)
Extensive agriculture is the main vector of environmental contamination. The aim of this study was to investigate the adsorption of chromium (III) metal ions from fertilizer wastewater using kaolin clay. The clay was characterized and used for the adsorption process in its natural and calcined forms. The major chemical components in the clay were silica (51.68%–52.38%) and alumina (25.7%–26.41%). The Brunauer–Emmett–Teller specific surface area was 98.84 m2/g for calcined and 70.84 m2/g for natural kaolin. The adsorption data were analyzed by isotherm and kinetic studies. Langmuir and Freundlich models were utilized for the analysis of the adsorption equilibrium isotherm. The adsorption capacity by calcined kaolin was 82.59 mg/g, while onto natural calcined was 63.56 mg/g. The experimental data fitted well into the Langmuir model for Cr(III) with regression coefficients (R2) of 0.96 and 0.86 for Cr(III) for calcined and natural kaolin clay, respectively. The pseudo-second-order kinetic model fitted well for chromium. This proves that kaolin clay is a good material for the removal of chromium ions from fertilizer wastewater.